Twenty-Four-Month-Olds' Perception of Word-Medial Onsets and Codas. Issue 4 (1st October 2016) - Wang, Yuanyuan; Seidl, Amanda
ABSTRACT: Recent work has shown that children have detailed phonological representations of consonants at both word-initial and word-final edges. Nonetheless, it remains unclear whether onsets and codas are equally represented by young learners since word edges are isomorphic with syllable edges in this work. The current study sought to explore toddler's sensitivity to onsets and codas without this overlap. This question is of theoretical interest since many theories of phonology suggest that onsets may be weighted more heavily than codas. We examined English-learning 24-month-olds' sensitivity to mispronunciations in word-medial onset and coda positions in a word learning task. We predicted that if children's sensitivity to onsets and codas is positionally constrained, then they should be more tolerant of Coda mispronunciations than onset ones. The results supported this prediction: children were less sensitive to coda mispronunciations than to onset mispronunciations in word-medial position, suggesting positionally driven biases in word processing.